TAXONOMY OF LANGUAGE TEACHING TECHNIQUES IN TEACHING READING - Isna Humaera (Institut Agama Islam Negeri Kendari, 2014)
English language teaching techniques have various categorization.Those techniques covering for main skills in English namely reading,listening, speaking and writing. The concept incorporatesclassification of type of activity that enables teachers to pick out thesequential activity within the lesson. Based on Behaviorism theory,language learning is a process of reinforcement repetition thatproposed three stages of learning that are called presentation,practice and production (PPP). The three step PPP aimed atdeveloping automatic habits largely through classroom processes ofmodeling, repetition, and controlled practice. Brown classifies thetaxonomy into three broad categories: controlled technique, semicontrolledtechnique, and free technique. Teachers have a dominantcontrol in controlled technique. In free technique, teachers are usuallyput into a less controlled role here, as students become free to becreative with their responses and interactions with other students.Semi controlled technique is the combination of the both categories.Keywords: taxonomy of language teaching, controlled technique,semi-controlled technique, free technique.